(untitled) (Bangladesh Journal of Agricultural Research, 2018)
Nine single cross promising maize hybrids and three check varieties (NK40, BHM9 and 900 MGold) were assessed for genotype environment interaction (GEI) and stability for the selection of promising one(s) in seven different locations of Bangladesh. The AMMI (additive main effects and multiplicative interaction) model was used to analyze the genotype-environment interaction over seven locations to select desired hybrid having higher yield and other potential attributes. Regarding genotypes (G), significant variation was found in all the characters except yield while environment (E) was found significant for all the characters. The environment of Gazipur was poor; Jamalpur, Hathazari, Ishurdi, Rahmatpur, Burirhat, and Jessore were positive environments for tested maize hybrids. Considering the mean, bi and S2di for all the parameters, it was evident that all the genotypes showed different response of adaptability under different environmental conditions. Among the hybrids E12 (900MG), E7(CML502 × CML491), E1(BIL95 × BIL28), E10 (NK40) and E2 (BIL95 × BIL31) were exhibited high yielder.Considering bi ̴1(regression co-efficient), S2di ̴ 0 (deviation from regression)and mean versace IPCA1 (fig1)indicated that hybrids E7and E1showed the higher yield as well as stable across locations. Bangladesh J. Agril. Res. 43(2): 301-307, June 2018